What Drives States to Raise Gas Tax Rates? An Empirical Analysis. (July 2022) - Chen, Can; Su, Min; Zhang, Ping
Gas taxes represent one of the most important revenue sources for state transportation funding. This study draws upon the theory of policy innovation and diffusion and examines the drivers of legislative decisions to directly increase state gas tax rates among 50 states from 2010 to 2018. Using a discrete event history analysis, this study finds that states raise gas tax rates in response to the growing funding needs of maintaining and improving the quality and performance of state highway infrastructure. Additionally, these findings suggest that state internal characteristics— poverty rate, personal income, rising gas prices, as well as the external influences of neighboring states affect the adoption of a gas tax rate hike.